Where is ambition in factor models of personality?. (1st February 2017) - Jones, Ashley Bell; Sherman, Ryne A.; Hogan, Robert T.
Abstract: Ambition is a personality construct with important implications for individual differences in educational and career success and status attainment. Although the best-known factor models of personality—the Five Factor Model (FFM) and the HEXACO—are widely regarded as comprehensive, they seem not to include ambition. The current study concerns whether ambition can be found in the HEXACO and FFM. Using data from the Eugene-Springfield Community Sample, our results indicate that ambition can be partially captured with a combination of HEXACO (or FFM) facets, especially Social Boldness and Liveliness (eXtraversion) and Diligence and Prudence (Conscientiousness), none of which, however, concern competitiveness, a key component of ambition. Overall, these findings suggest that important personality constructs are not found in conventional factor models of personality.